2014 IEEE/ASME International Conference on Advanced Intelligent Mechatronics 2014
DOI: 10.1109/aim.2014.6878271
|View full text |Cite
|
Sign up to set email alerts
|

An approach for obtaining unique kinematic solutions of a spherical parallel manipulator

Abstract: In this paper an approach for obtaining unique solutions to forward and inverse kinematics of a spherical parallel manipulator (SPM) system with revolute joints is proposed. Kinematic analysis of a general SPM with revolute joints is revisited and the proposed approach is formulated in the form of easy-to-follow algorithms that are described in detail. A graphical verification method using SPM computer-aideddesign (CAD) models is presented together with numerical and experimental examples that confirm the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Therefore, eight possible solutions are provided for the inverse kinematic problem. In this paper, the algorithm presented in [18] (to which we refer the reader for details), is used. This algorithm is defined in order to employ only one of the eight solutions at each sampling instant, also maintaining the same working mode during the whole robot motion.…”
Section: B Spm Inverse Kinematicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, eight possible solutions are provided for the inverse kinematic problem. In this paper, the algorithm presented in [18] (to which we refer the reader for details), is used. This algorithm is defined in order to employ only one of the eight solutions at each sampling instant, also maintaining the same working mode during the whole robot motion.…”
Section: B Spm Inverse Kinematicsmentioning
confidence: 99%
“…Thus, there is a need for general control laws that can directly take these constraints into account. In [17], an off-line framework was proposed for generating optimal motor trajectories for general 3-DOF RRR SPMs, based on the kinematics analysis reported in [18]. A feasible configuration space for the SPM was first defined by using numerical procedures, in order to guarantee the absence of singularities and collisions between links during the motion of the manipulator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming that the same home SPM assembly and coordinate system are considered for obtaining unique solutions to the manipulator kinematics, vector θ can be found knowing vectors v i , i = 1, 2, 3, corresponding to the current orientation of the SPM top mobile platform, by determining unique inverse kinematic solutions, as proposed by the authors in [41].…”
Section: Unique Forward Kinematicsmentioning
confidence: 99%
“…Experimental demonstration of the proposed framework using a 3D printed prototype of the Agile Wrist SPM with three servomotors is given in Section VI, which also includes a discussion of the results. The first phase of the framework proposed in this paper is a development of the authors' preliminary work [41], that also reported an approach for obtaining a unique inverse kinematic solution, a graphical verification method using SolidWorks CAD software and numerical examples considering a specific Agile Wrist SPM.…”
Section: Introductionmentioning
confidence: 99%